The Relationship between Health Belief Model Applications with Smoking Quitting Behavior: A Meta-Analysis - Gadis Nur Anggreani; Faridah Nurhayati; Herawati Prianggi (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Smoking is a habit of smoking cigarettes that is carried out in daily life, cigarettes are also a necessity that cannot be avoided for people who have a tendency to cigarettes. HBM is a model of individual health beliefs in determining the actions to be taken and is explained as a concept formulated with the aim of understanding why individuals do or do not perform various healthy behaviors. Therefore, this study aimed to determine the level of effectiveness of the Health Believe Model (HBM) application in the decision to quit smoking.Subjects and Method: This article was compiled with a systematic review and meta-analysis study. This study uses the PICO Model. The meta-analysis study was conducted by searching for articles from databases in electronic form including PubMed, Springer Link, Elsevier and Google Scholar.